(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, approaching modern sources of legal consciousness, with the help of analysis, analysis-synthesis and other methodological methods, their role in the formation of a legal democratic state and civil society was studied, and the state was analyzed as their main subject.